The acceptability of intimate partner violence screening and response among refugee women accessing Australian resettlement services. - Nigel Spence; Jo Spangaro; Nicola Man; Jacqui Cameron; Kelsey Hegarty; Jane Koziol-McLain; Tadgh McMahon; Astrid Perry-Indermaur; Chye Toole-Anstey; Jeannette Walsh; Anthony Zwi (PLoS ONE)
Screening and response for intimate partner violence (IPV) is recommended for women in priority populations and is implemented in health services across diverse jurisdictions. Most women experiencing IPV strongly support screening, however this is untested with refugee women in resettlement contexts. Around one third of refugee women in Australia experience IPV and face multiple post-migration challenges. SAHAR (Safety and Health after Arrival) tested IPV screening using the ACTS tool, brief intervention, and referral with women accessing four settlement support services. Women attending sites during the study period were invited to participate in a three month follow up survey with participation by 321/375 women recruited (86%). Acceptability of IPV screening was assessed against (i) levels of comfort with the IPV screening questions and (ii) strength of agreement/disagreement with settlement services asking women about being frightened, controlled or hurt by their partners. Of participants who recalled the screening, 93% reported being very or moderately comfortable with being asked the questions (89% who had experienced IPV; 94% of those with no IPV identified). For all participants, 84% strongly or somewhat agreed with services asking the questions, with no significant difference in agreement between disclosing and non-disclosing groups. Those with no recall of the questions had lower overall agreement and higher disagreement than those who recalled the questions (88% and 10%). Acceptability was not associated with age, country of origin, household composition, time since arrival or number of prior service visits. Participants identified 'care shown by the worker', 'talking to someone in my own language', 'trust in the privacy of the service', and 'talking to a female worker' as the factors most important for encouraging discussion of IPV. High acceptance of IPV screening by refugee women supports consideration of implementation across settlement services, a key access point for refugee women with diverse needs.